Through-thickness perforated steel plates optimized for ballistic impact applications - Francisco Javier Ramírez-Gil (Elsevier, 2021)
A tradeoff between lightweight and ballistic resistance is common when designing ballistic protection systems for the transportation market. Steel is one of the most affordable and widely used armor materials due to its cost and manufacturing advantages. However, its high density compared to ceramics and composites reduces its eligibility. Therefore, a weight reduction of steel plates is achieved here by inserting holes distributed throughout the plate thickness. Two approaches are proposed. The first creates cylindrical hole patterns parametrically based on the functionally graded concept found in biological structures subjected to impact loads. The second approach uses the topology optimization method to design the free-shaped hole pattern through thickness. The designed plates are manufactured and evaluated numerically and experimentally. Ballistic impact tests are performed according to the NIJ 0108.01 standard, and the results are analyzed using design of experiments. Several nondestructive tests are applied to measure the damage on the impacted plates. Results show that the performance of the topology optimized designs and the solid plates is statistically equivalent, while the parametric plates are partially penetrated. This is an important result to establish a new design methodology in a complex field where topology optimization has been little explored.